Lower and upper bound form of outage probability in one-way AF full-duplex relaying network under impact of direct link - Phu Tran Tin; Van-Duc Phan; Le Anh Vu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
This paper proposed and investigated the one-way amplify-and-forward (AF) full-duplex relaying network under impact of direct link. For the system performance analysis, the exact and lower and upper bound form of the system outage probability (OP) are investigated and derived. In this system model, authors assume that the E uses the MRC (maximal ratio combining) technique. Finally, we can see that the analytical and the simulation values overlap to verify the analytical section using the Monte Carlo simulation. Also, we investigate the influence of the system primary parameters on the proposed system OP.